Efficacy of Bat Guano on Growth and Yield of Some Hybrid Sunflower (Helianthus annus, L.) Cultivars in Sudan - H. M. Adam, Abubaker; Adam, Abdalla; M.A Magid, Faiza (Journal of Agronomy Research, 2020)
Today; there is an increasing demand for fertilizers due to the intensive and extensive agricultural activity to meet the ever increasing demand for food and fiber by the rapid world population expansion. This study is mainly concern with the Bat Guano which is usually collected from the Caves. This experiment was conducted at the Farm of the College of Agriculture, University of Bahri, Alkadaro, Khartoum North-Sudan during the period from July to November, 2017 with the objective to investigate the efficacy of Bat Guano and Nitrogen fertilizer on growth and yield of Serena and Opera (Helianthusannus, L.) Hybrid Sunflower cultivars. The study was based on split-plot experiment in randomized complete block design (RCBD) with four (4) replications. Data pertaining Plant Height (cm), Leaf Number (LN), Leaf Area (LA), Leaf Area Index (LAI) and Seed Weight (SW) were studied. The said data were analyzed using Statistic 8- software. The results reflected significant increase in plant height (F= 6.05, P < 0.0001, leaf number (F=2.37, P<0.0388), leaf area (F= 7.44, P<0.001), leaf area index (F= 6.53, P < 0.0001) and seed weight of both Sunflower cultivars respectively due to application of Guano and Nitrogen fertilizer compared to the control. It also reflected non-significant difference between all studied traits as application of either Guano or Nitrogen fertilizer. Moreover, all studied characters of the two cultivars have similarly responded to the application of the two types of fertilizers. Further studies are recommended to assess the benefits from the use of Bat Guano as a fertilizer.
Keywords: Bat Guano; Hybrid Sunflower; Growth and Yield; Nitrogen Fertilizer; Sunflower